2017
DOI: 10.1002/elan.201600799
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Characterizations of four Main Redox–metabolites of Pseudomonas Aeruginosa

Abstract: Bacterial identification is of first importance in clinic nowadays. For few years, electrochemistry appears as a reliable route for characterizations outside of laboratories. Nowadays, researchers mainly focus on the opportunistic pathogen Pseudomonas aeruginosa because of its production of the Pyocyanin toxin which has an electrochemical case study behavior. Other P. aeruginosa secreted molecules are also studied in a lesser extent. This work deals with the systematic electrochemical characterizations in apro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 29 publications
6
35
1
Order By: Relevance
“…Hence, the ratio i pa /i pc at different scan rates was evaluated ( Figure 5 d). The behavior confirmed that the reversal oxidation process I a was controlled by diffusion, with adsorption of PYO significantly reduced over the electrode surface [ 10 , 47 ]. Finally, considering low scan rates, where the adsorption process was not presented, a value of |Δ E p | = 0.035 V was calculated, which indicated a two-electron transfer, according to Equation (6).…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Hence, the ratio i pa /i pc at different scan rates was evaluated ( Figure 5 d). The behavior confirmed that the reversal oxidation process I a was controlled by diffusion, with adsorption of PYO significantly reduced over the electrode surface [ 10 , 47 ]. Finally, considering low scan rates, where the adsorption process was not presented, a value of |Δ E p | = 0.035 V was calculated, which indicated a two-electron transfer, according to Equation (6).…”
Section: Resultsmentioning
confidence: 61%
“…The redox process for PYO was studied through cyclic and square wave voltammetries. PYO and other redox metabolites included in the secretome of P. aeruginosa could be used as electrochemical biomarkers to detect its presence in a bacterial culture supernatant [ 10 ]. Furthermore, P. aeruginosa is considered an electrogenic microorganism and is used in bioelectrochemical systems for electrical energy production, carried out by direct electron transfer (through cytochromes in outer membrane or bacteria pili) and indirect electron transfer (through secondary metabolites excreted by bacteria).…”
Section: Introductionmentioning
confidence: 99%
“…This strategy has been reported in many occasions for the detection of PYO [128,129], one of the main virulence factors regulated by the QS, which shows well-known redox properties. However, the electrochemical behaviour of AQs has been only partially known until very recently [130]. Thus, HHQ shows only one purely irreversible oxidation wave at high potential around + 0.99 V over the first CV scan when using glassy carbon (GC) working electrodes (1 mm diameter) and Ag/Ag + reference electrodes in organic media.…”
Section: Electrochemical Sensorsmentioning
confidence: 99%
“…Gram-negative bacteria use HSLs as signaling molecules to regulate gene expression in a concentration-dependent manner. However, some strains produce additional non-homoserine lactone molecules, such as the PQS in P. aeruginosa [31,32]. Most Gram-negative systems contain a LuxI/LuxR QS network homolog.…”
Section: Qs In Gram-negative Pathogensmentioning
confidence: 99%
“…PQS has an oxidation and reduction peak at +0.233 V and +0.178 V, respectively. Pyocyanin can be detected via electrochemically with symmetrical peaks at −0.16 V and an irreversible oxidation peak at +0.8 V [32].…”
Section: Gram-negativementioning
confidence: 99%